Microwave-assisted green synthesis of silver nanoparticles using Mitragyna parvifolia bark extract and their biological activities: an economical and environment-friendly approach - Dwivedi A.; Das S.; Tiwari V.; Yadav V.; Jain S.K.; Mandal V.; Mukherjee S.; Satpathy S.; Mohapatra D.; Sahu A.N.; Satpathy M.P.; Mehta S.K.; Singh S.; Goyal M.; Kazi M.; Hussain M.D.; Patra A. (My University, 2025)
Nowadays, nanotechnology is extensively employed in the medical profession. In this study, we used the aqueous extract of the bark of Mitragyna parvifolia to synthesize silver nanoparticles (AgNPs) by microwave-assisted green synthesis. The synthesis of AgNPs was confirmed by visual color change to brown color and characteristic surface plasmon resonance peak at 432 nm. The hydrodynamic diameter of the AgNPs was 171.81 nm having a zeta potential of −24.14 mV; Fourier Transmission Infrared Spectroscopy confirmed the presence of different functional groups on the NP surface; Scanning Electron Microscope and High-Resolution Transmission Electron Microscopy indicated predominantly circular shape of nanoparticle; Selected Area Electron Diffraction and X-ray Diffraction analyses determined the crystalline structure of AgNPs. Energy-Dispersive X-ray indicated the elemental composition and formation of AgNPs. The AgNPs were screened at different concentrations for antioxidant activity, antimicrobial, and anticancer potential in breast cancer cells (MCF-7 and MDA-MB-231). The AgNPs exhibited remarkable antioxidant, antimicrobial, and anticancer activities. The sedative and antinociceptive activities were also tested on Swiss albino mice, which showed mild sedative and very potent antinociceptive activity. However, detailed mechanistic studies are warranted in the future for clinical application of the AgNPs as a biologically active agent as well as a carrier for drug delivery. © 2024 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.